DIRECTIONS FOR DETERMINING THE CORRECTNESS OF ESTIMATED VALUES IN THE AUDIT OF FINANCIAL STATEMENTS - Anvar Ziyadullayevich Avlokulov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the importance and necessity of determining the correctness of estimated values in the audit of financial statements. As a result of the research conducted, proposals were developed to determine the correctness of estimated values.